NOTES on THE BIOLOGY and BEHAVIOUR of THE JEWEL WASP, AMPULEX COMPRESSA (FABRICIUS, 1781) (HYMENOPTERA; AMPULICIDAE), IN THE LABORATORY, INCLUDING FIRST RECORD of GREGARIOUS REPRODUCTION - Paterson Fox, Eduardo Goncalves [UNESP]; Bressan-Nascimento, Suzete; Eizemberg, Roberto (Amer Entomol Soc, 2009)
A colony of the solitary parasitoid ampulicid wasp Ampulex compressa was established under laboratorial conditions. A total of 23 wasps were reared, which attacked about 80 cockroach hosts. Wasps' longevity and development mean times recorded were 55.85 +/- 26.09 and 43.17 +/- 3.58 days, respectively. of the attacked cockroaches, 60% yielded ordinary solitary brood (sexual ratio approximately 1:1), 23.75 % failed to hatch, and 16.25 % presented one egg over each middle coxa. The two eggs laid on one prey always produced two dwarf male wasps. Laying two eggs on one prey has never been reported before. Not all cockroaches were attacked by the wasps, and some avoided being stung by aggressively reacting against the wasps' approaches. We consider these finds to demonstrate the plasticity of the host-handling behaviour of A. compressa, illustrating how synovigenic parasitoids can adapt rapidly to surrounding conditions.
Keywords: Periplaneta americana; jewel wasp; Ampulex compressa; Hymenoptera; Ampulicidae; laboratory; parasitoid; brood size; reproductive behaviour; gregarious reproduction; two eggs on one prey; solitary reproduction